Pentaerythritol phosphate dihydric alcohol as well as preparation method and application thereof

The cyclic pentaerythritol phosphite diol prepared by transesterification reaction was introduced into the polyurethane resin as a modifier, which solved the problem of insufficient weather resistance of the polyurethane resin-based composite material under outdoor working conditions, and achieved the material's photo-aging and water resistance Improved resolution and flame retardant performance.

CN119490530APending Publication Date: 2025-02-21南京聚发新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411647000.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The weather resistance performance of polyurethane resin-based composites still face challenges in outdoor working environments, especially the lack of resistance to ultraviolet aging, humidity and heat aging and hydrolysis resistance.

Method used

Pentaerythritol phosphite diol with a cyclic structure was prepared by transesterification reaction and introduced into a polyurethane resin as a modifier to improve the photoaging resistance, hydrolysis resistance and flame retardant properties of the material.

Benefits of technology

This method not only does not affect the mechanical properties of the polyurethane resin, but also significantly improves the photoaging, hydrolysis and flame retardant properties of the material, reducing production costs and environmental burdens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490530A_ABST
    Figure CN119490530A_ABST
Patent Text Reader

Abstract

The invention discloses phosphorous acid pentaerythritol ester dihydric alcohol as well as a preparation method and application thereof. The phosphorous acid pentaerythritol ester diol has a structure as shown in a formula (I): # imgabs0 #, in the formula (I), R1 is a C2-C18 straight chain alkyl group, a branched chain alkyl group, a cyclic alkyl group or an aryl group, or HO-R1-OH is polyether diol or polyester diol with the molecular weight of 200-1000g / mol. The flame retardant is introduced into polyurethane resin as a modifier, so that the resin material is endowed with excellent light aging resistance, hydrolysis resistance and flame retardance. In addition, the preparation process is simple, the equipment investment is low, the solid catalyst can be repeatedly used, and the production cost and the environmental burden are greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer synthesis, resin and fiber-reinforced composite material preparation, in particular to a pentaerythritol phosphite diol and a preparation method and application thereof. Background Art

[0002] Polyurethane resin has been increasingly used in the preparation and production of fiber-reinforced resin-based composite materials in recent years due to its advantages of wide raw material sources, high production efficiency and good environmental protection, such as polyurethane-based composite frames prepared by pultrusion and large pipes and poles prepared by winding. Such products need to serve in outdoor conditions for many years, and have very high requirements for the material's resistance to ultraviolet aging, resistance to wet and hot aging, and resistance to hydrolysis. The mainstream solution currently in use is to use aromatic polyurethane resin to produce products, and then spray fluorocarbon paint on the surface of the product to achieve the purpose of protection. The risk of this solution is that during the transportation, installation and use of the product, it is inevitable that the fluorocarbon coating will be damaged by bumps, scratches by bird claws and gnawing by animals. Once the coating is damaged, the damaged area will be corroded by small molecules such as ultraviolet light, moisture and oxygen. As time goes on, the erosion surface expands, and the coating will fall off regionally as a whole, further accelerating the erosion of the body and the decline of material performance.

[0003] Some technologies have also attempted to formulate aliphatic polyurethane resins and solve the above-mentioned problems by adding flame retardants, anti-aging agents, etc. However, most of the flame retardants and anti-aging agents on the market are additives. Adding a large amount of them can easily lead to a sharp decline in mechanical properties. In addition, there is the problem of migration of additives during the use of the product. After a long period of migration, the product loses the corresponding function.

[0004] In summary, the weather resistance of polyurethane resin-based composite materials in outdoor working conditions still faces many challenges. How to improve its light aging and hydrolysis resistance while ensuring the mechanical properties of the material is a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above problems, the present invention proposes a new solution. Pentaerythritol phosphite diol or a mixture thereof is prepared by ester exchange reaction, and introduced into polyurethane resin as a modifier. This pentaerythritol phosphite diol with a ring structure not only has reaction activity and does not affect the mechanical properties of polyurethane resin, but also its unique chemical structure gives the material excellent light aging resistance, hydrolysis resistance and flame retardant properties. In addition, the preparation process of the present invention is simple, the equipment investment is low, and the solid catalyst can be reused, which greatly reduces the production cost and environmental burden.

[0006] The following is the technical solution of the present invention:

[0007] The present invention provides a pentaerythritol phosphite diol, wherein the pentaerythritol phosphite diol has a structure as shown in formula (I):

[0008]

[0009] In formula (I), R1 is C2-C 18 The straight-chain alkyl, branched-chain alkyl, cyclic alkyl or aryl group is selected from the group consisting of: HO-R1-OH and HO-R2-OH; or HO-R1-OH is a polyether diol or polyester diol having a molecular weight of 200-1000 g / mol.

[0010] Furthermore, the polyether diol is polypropylene oxide ether diol; the polyester diol is one of polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexanediol adipate diol.

[0011] The present invention also provides a method for preparing the above-mentioned pentaerythritol phosphite diol, which comprises the following steps:

[0012] Adding triester phosphite, transesterification catalyst and pentaerythritol into a three-necked flask connected to a condenser to receive the fraction, sealing, heating to 120-160° C., reacting for 6 hours, and continuing to add diol at the same temperature, and continuing to react for 6 hours. After almost no fraction is evaporated, filtering out the transesterification catalyst to obtain pentaerythritol phosphite diol or a mixture A thereof; wherein the mixture A contains ≥78wt% of pentaerythritol phosphite diol;

[0013] The phosphite triester structure is as follows:

[0014] R is a C1-C4 aliphatic chain.

[0015] In some embodiments of the present invention, the transesterification catalyst is selected from the 8XMP model of Tulsimer Company of the United States or the A-21 model product of Jiangyin Nanda Synthetic Company.

[0016] The present invention provides a two-component aliphatic polyurethane resin, wherein the polyurethane resin is prepared by mixing a component S1 and a component S2, wherein the component S1 contains the pentaerythritol phosphite diol according to claim 1, and the component S2 is an isocyanate or a prepolymer of an isocyanate.

[0017] The present invention provides a two-component aliphatic polyurethane resin, which is prepared by mixing a component S1 and a component S2, wherein the ratio of the molar number of reactive hydroxyl groups in the component S1 to the molar number of reactive isocyanate in the component S2 is (1.0-1.1):1.0; the component S1 comprises the following raw materials in parts by weight:

[0018]

[0019] The pentaerythritol phosphite diol has a structure as shown in formula (I):

[0020]

[0021] In formula (I), R1 is C2-C 18 A linear alkyl group, a branched alkyl group, a cyclic alkyl group or an aryl group, or HO-R1-OH is a polyether diol or a polyester diol having a molecular weight of 200-1000 g / mol;

[0022] The S2 component is isocyanate or a prepolymer of isocyanate;

[0023] The mixture A contains ≥78 wt % of pentaerythritol phosphite diol.

[0024] For example, the polyether diol is polypropylene oxide ether diol, and the polyester diol is one of polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexylene adipate diol.

[0025] In some embodiments of the present invention, the hydroxyl value of the pentaerythritol phosphite diol is 40 to 300 mgKOH / g. The hydroxyl value of the S1 component is 276 to 411 mgKOH / g.

[0026] In some embodiments of the present invention, the polyether polyol is one or more polypropylene oxide ether polyols having a functionality f=3-6 and a hydroxyl value of 280-650 mgKOH / g.

[0027] In some embodiments of the present invention, the release agent is selected from one of 1948MCH, 1968MCH of AXEL Corporation of the United States, HB-550, and HB-550D of Ken-Trend Corporation of the United States; the catalyst A is an organic tin compound with low catalytic activity, specifically, the catalyst A is selected from one of UL-6, UL-28, and UL-29 of Momentive Corporation of the United States; the flame retardant is selected from one of triethyl phosphate, tris-(1,3-dichloroisopropyl) phosphate, tris-(chloroisopropyl) phosphate, and tris(butoxyethyl) phosphate.

[0028] The present invention prepares pentaerythritol phosphite diol by transesterification reaction, and a large amount of expensive advanced equipment, such as high vacuum system, etc., is required to achieve the theoretical reaction effect. Although more raw materials of triester phosphite, such as triphenyl phosphite, etc., can be selected, the high vacuum system can separate the byproduct phenol by distillation at high temperature, but the product manufacturing cost is too high. Therefore, the present invention preferably uses triester phosphite of low boiling point byproducts (methanol, ethanol, propanol and butanol) as raw materials to prepare pentaerythritol phosphite diol by transesterification reaction.

[0029] Preferably, the preparation method of the pentaerythritol phosphite diol is as follows: heating the triester of phosphite, the transesterification catalyst and the pentaerythritol to 120-160° C., reacting until substantially no fraction is evaporated, continuing the reaction for a period of time, and then continuing to add the diol at the same temperature, continuing the reaction until substantially no fraction is evaporated, and continuing the reaction for a period of time, filtering out the transesterification catalyst, and obtaining a reaction product containing ≥80wt% of the pentaerythritol phosphite diol; the molar ratio of the added amount of the triester of phosphite, the pentaerythritol and the diol is 1:0.5:1, and the added amount of the transesterification catalyst is 5wt% of the added amount of the triester of phosphite; the transesterification catalyst is a solid alkaline catalyst; the structure of the triester of phosphite is as follows:

[0030] R is a C1-C4 aliphatic chain.

[0031] The theoretical reaction process is as follows:

[0032]

[0033] From the perspective of application, even if the reaction process is not very complete, the product does not affect the actual application effect, and can still be linked to the solidified material network in a covalent bond through the reaction of hydroxyl and isocyanate, but the investment in equipment is very low, as long as the by-products can be distilled and separated. Therefore, considering the product manufacturing cost and downstream application effect, the present invention preferably uses phosphite triesters of low-boiling point by-products (methanol, ethanol, propanol and butanol) as raw materials to prepare pentaerythritol phosphite diol.

[0034] In some embodiments of the present invention, the transesterification catalyst is selected from the 8XMP model of Tulsimer Company of the United States or the A-21 model product of Jiangyin Nanda Synthetic Company.

[0035] In some embodiments of the present invention, the diol is C2-C 18The invention relates to an aliphatic diol or a polyether diol or polyester diol having a molecular weight of 200-1000 g / mol. Specifically, the polyether diol is polypropylene oxide ether diol, and the polyester diol is one of polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol, and polyhexane adipate diol.

[0036] In some embodiments of the present invention, the S2 component is a hexamethylene diisocyanate trimer or an isocyanate prepolymer. The NCO% content of the S2 component is 16% to 25%. The isocyanate prepolymer is prepared by reacting an aliphatic isocyanate with a polymer diol at 80 to 100°C for 2 to 6 hours. Specifically, the aliphatic isocyanate is selected from one of isophorone diisocyanate, hexamethylene diisocyanate, and dicyclohexyl methyl diisocyanate; the polymer diol is a polyoxypropylene ether diol with a molecular weight of 400 to 1000 g / mol.

[0037] The pentaerythritol phosphite diol with a ring structure prepared by the present invention has reaction activity and will not affect the mechanical properties of polyurethane resin; the P atom therein has strong reducing property and is easily oxidized by free radicals excited by ultraviolet light or high temperature, thus giving the material excellent ultraviolet resistance and heat resistance; the ring structure enables only the heterocyclic ring to be opened when PO is hydrolyzed, and the molecular chain is not broken, thereby improving the hydrolysis resistance of the material; the high content of the P element itself gives the resin and the composite material excellent flame retardant properties; the solid catalyst can be separated only by filtering, and can be kept for next reuse (can be reused about 6-10 times), and the problem of excessively fast subsequent polyurethane reaction activity caused by the residue of the alkaline catalyst after the reaction is completed is avoided.

[0038] The present invention also provides a method for preparing the above-mentioned aliphatic polyurethane resin, comprising the following steps: mixing component S1 and component S2, and obtaining the polyurethane resin after curing;

[0039] The preparation of component S1 comprises the following steps: (1) adding triester phosphite, transesterification catalyst and pentaerythritol into a three-necked flask connected to a condensing device to receive the distillate, sealing, heating to 120-160°C, reacting for 6 hours, and continuing to add diol at the same temperature, and continuing to react for 6 hours. After almost no distillate is evaporated, filtering out the transesterification catalyst to obtain pentaerythritol phosphite diol, and testing its hydroxyl value; (2) adding other different types of polyether polyols according to the hydroxyl value data in step (1), and adjusting the hydroxyl value to 400-450 mgKOH / g; (3) continuing to add auxiliary agents and stirring evenly, the auxiliary agents include a release agent, a catalyst A and a flame retardant; the molar ratio of the added amounts of triester phosphite, pentaerythritol and diol in step (1) is 1:0.5:1, and the added amount of the transesterification catalyst is 5wt% of the added amount of triester phosphite;

[0040] The phosphite triester structure is as follows:

[0041] R is a C1-C4 fatty chain;

[0042] The transesterification catalyst is a solid alkaline catalyst;

[0043] The diol is C2-C 18 aliphatic diols or polyether diols or polyester diols having a molecular weight of 200-1000 g / mol.

[0044] The present invention also provides a fiber-reinforced material, which is made by compounding the above-mentioned aliphatic polyurethane resin and fiber. Specifically, the resin is compounded with fiber by pultrusion process to prepare continuous fiber-reinforced composite material profiles, such as solar frames, etc.; or the resin is compounded with fiber by winding process to prepare outer fiber-reinforced materials for large pipelines such as electric poles and signal towers, etc. Both can provide products with protection against light, heat, moisture and fire.

[0045] Beneficial effects:

[0046] Compared with the prior art, the present invention has the following advantages: (1) pentaerythritol phosphite diol or a mixture thereof is prepared by ester exchange reaction, and introduced into polyurethane resin as a modifier. This pentaerythritol phosphite diol with a cyclic structure not only has reaction activity and does not affect the mechanical properties of polyurethane resin, but also its unique chemical structure gives the material excellent light aging resistance, hydrolysis resistance and flame retardant properties. The pentaerythritol phosphite diol ester of the present invention can completely replace the additive cyclic flame retardant, effectively avoiding the problem of flame retardant migration during the use of polyurethane products. In addition, the preparation process of the present invention is simple, the equipment investment is low, and the solid catalyst can be reused, which greatly reduces the production cost and environmental burden. (2) The raw materials of the present invention are widely available. Pentaerythritol and triester phosphite are both low-priced and in sufficient supply. The other polyurethane-related raw materials in my country have sufficient or even excess production capacity. The above gives the polyurethane resin prepared by the present invention the characteristic of low cost; (3) Even if the composite material prepared by the present invention is bumped or damaged by animals, the damage point will not extend and the main performance will not change, which solves the problem of the precipitous drop in the performance of the composite material after the fluorocarbon coating is damaged; (4) Under complex operating conditions, the resin and fiber-reinforced composite material prepared by the present invention are resistant to multiple common aging methods. During service, they always have a higher performance retention rate compared with similar products. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with the examples, and the examples of the examples are intended to explain the present invention and should not be construed as limiting the present invention. Where specific techniques and reaction conditions are not specified in the examples, the techniques or conditions described in the literature in the art or the product instructions can be used. Any reagent, instrument or equipment not specified by the manufacturer can be obtained commercially. The polyether polyols mentioned in the examples are polypropylene oxide ether polyols.

[0048] Example 1

[0049] Accurately weigh 1000mol trimethyl phosphite and add it to the reactor, then add 5% of its weight of A-21 solid base catalyst from Nanda Synthetic Company and 500mol pentaerythritol, heat to 120°C, open the condenser at the same time, receive the by-product methanol (boiling point 65°C), react for about 4h until no new fraction is evaporated, continue to react for 2h, then add 1000mol ethylene glycol, and continue to receive the by-product methanol, also react for about 4h until no new fraction is evaporated, continue to react for 2h, cool down, filter to obtain a pentaerythritol phosphite diol mixture, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 300mgKOH / g, and the theoretical hydroxyl value is 355mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 85%.

[0050] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportion:

[0051]

[0052] The hydroxyl value of S1 component is 400 mgKOH / g;

[0053] The S2 component uses commercially available hexamethylene diisocyanate trimer (HDI trimer, HT100 brand of Wanhua Company, NCO% = 22.5%);

[0054] The weight ratio of component S1 to component S2 is 100:133, calculated based on the molar ratio of hydroxyl to isocyanate being 1.0:1.0.

[0055] The pultrusion process was used to prepare 2mm*200mm*200mm full glass fiber yarn sheets, and samples were prepared for performance testing.

[0056] Example 2

[0057] Accurately weigh 1000mol triethyl phosphite and add it to the reactor, then add 5% of its weight of Tulsimer's 8XMP type solid base catalyst and 500mol pentaerythritol, heat to 140°C, open the condenser at the same time, receive the by-product ethanol (boiling point 76°C), about 4.5h or so, no new fraction is evaporated, continue to react for 1.5h, then add 1000mol hexanediol, and continue to receive the by-product ethanol, also react for about 4.5h, no new fraction is evaporated, continue to react for 1.5h, cool down, filter to obtain a pentaerythritol phosphite diol mixture, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 222mgKOH / g, and the theoretical hydroxyl value is 262mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 85%.

[0058] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportions:

[0059]

[0060] The hydroxyl value of S1 component is 276 mgKOH / g;

[0061] The S2 component is prepared using isophorone diisocyanate (IPDI) and polypropylene oxide ether diol. 400 kg of polyether diol with a molecular weight of 400 g / mol is added to the reactor, the temperature is raised to 100° C., 1437 kg of IPDI is added, and the reaction is carried out for 2 hours to obtain a prepolymer with an NCO% of 25%.

[0062] The S1 component and the S2 component were mixed with resin in a weight ratio of 100:75, calculated based on the molar ratio of hydroxyl to isocyanate of 1.1:1.0. The winding process was used to prepare equal-diameter poles with a length of 15m, an outer diameter of 250mm, and an inner diameter of 230mm. After curing, 50mm*100mm samples were cut from the poles for UV light aging test.

[0063] Example 3

[0064] Accurately weigh 1000mol tripropyl phosphite and add it to the reactor, then add 5% of its weight of A-21 solid base catalyst from Nanda Synthetic Company and 500mol pentaerythritol, heat to 150°C, open the condenser at the same time, receive the by-product propanol (boiling point 82.5°C), about 5h or so, no new fraction is evaporated, continue to react for 1h, then add 1000mol stearyl glycol, and receive the by-product propanol, also react for about 5h, no new fraction is evaporated, continue to react for 1h, cool down, filter to obtain a pentaerythritol phosphite diol mixture, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 110mgKOH / g, and the theoretical hydroxyl value is 135mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 81%.

[0065] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportions:

[0066]

[0067]

[0068] The hydroxyl value of S1 component is 380 mgKOH / g;

[0069] The S2 component is prepared using dicyclohexylmethyl diisocyanate (H-MDI) and polypropylene oxide ether diol. 1000kg of polyether diol with a molecular weight of 1000g / mol is added to the reactor, the temperature is raised to 80°C, 1479kg of IPDI is added, and the reaction is carried out for 6h to obtain a prepolymer with an NCO% of 16%.

[0070] The weight ratio of component S1 to component S2 is 100:170, calculated based on the molar ratio of hydroxyl to isocyanate being 1.05:1.0.

[0071] The pultrusion process was used to prepare 2mm*200mm*200mm full glass fiber yarn sheets, and samples were prepared for performance testing.

[0072] Example 4

[0073] Accurately weigh 1000mol tributyl phosphite () and add it to the reactor, then add 5% of its weight of Tulsimer's 8XMP solid base catalyst and 500mol pentaerythritol, heat to 160°C, open the condenser at the same time, receive the by-product butanol (boiling point 117.5°C), about 5.5h or so, no new fraction is evaporated, continue to react for 0.5h, continue to add 1000mol polypropylene oxide ether diol (Mw: 200g / mol), and receive the by-product butanol, also react for about 5.5h, no new fraction is evaporated, continue to react for 0.5h, cool down, filter to obtain a pentaerythritol phosphite diol mixture, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 140mgKOH / g, and the theoretical hydroxyl value is 170mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 82%.

[0074] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportions:

[0075]

[0076] The hydroxyl value of the S1 component is 331 mgKOH / g.

[0077] The S2 component is prepared using hexamethylene diisocyanate (HDI) and polypropylene oxide ether diol. 600 kg of polyether diol with a molecular weight of 600 g / mol is added to the reactor, the temperature is raised to 90°C, 680 kg of HDI is added, and the reaction is carried out for 4 hours to obtain a prepolymer with an NCO% of 20%.

[0078] The weight ratio of component S1 to component S2 is 100:124, calculated based on the molar ratio of hydroxyl to isocyanate being 1.0:1.0.

[0079] The pultrusion process was used to prepare 2mm*200mm*200mm full glass fiber yarn sheets, and samples were prepared for performance testing.

[0080] Example 5

[0081] Accurately weigh 1000mol tributyl phosphite and add it to the reactor, then add 5% of its weight of Tulsimer's 8XMP solid base catalyst and 500mol pentaerythritol, heat to 160°C, open the condenser at the same time, receive the by-product butanol (boiling point 117.5°C), about 5.5h, no new fraction evaporates, continue to react for 0.5h, continue to add 1000mol poly (neopentyl adipate glycol) diol (Mw: 600g / mol), and receive the by-product butanol, also react for about 5.5h, no new fraction evaporates, continue to react for 0.5h, cool down, filter to obtain a mixture of pentaerythritol phosphite diols, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 60mgKOH / g, and the theoretical hydroxyl value is 77mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 78.0%

[0082] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportions:

[0083]

[0084] The hydroxyl value of the S1 component is 411 mgKOH / g.

[0085] The S2 component is commercially available hexamethylene diisocyanate trimer (HDI trimer, TPA100 brand of Asahi Chemical Co., Ltd., Japan, NCO%=22.5%).

[0086] The weight ratio of component S1 to component S2 is 100:130, calculated based on the molar ratio of hydroxyl to isocyanate being 1.05:1.0.

[0087] The winding process was used to prepare equal-diameter poles with a length of 15m, an outer diameter of 250mm, and an inner diameter of 230mm. After curing, 50mm*100mm samples were cut from them for UV light aging tests.

[0088] Example 6

[0089] Accurately weigh 1000mol triethyl phosphite () and add it to the reactor, then add 5% by weight of Tulsimer's 8XMP solid base catalyst and 500mol pentaerythritol, heat to 140°C, open the condenser at the same time, receive the by-product ethanol (boiling point 76°C), about 4.5h or so, no new fraction evaporates, continue to react for 1.5h, continue to add 1000mol polyhexanediol adipate diol (Mw: 1000g / mol), and receive the by-product ethanol, also react for about 4.5h, no new fraction evaporates, continue to react for 1.5h, cool down, filter to obtain a pentaerythritol phosphite diol mixture, and collect the solid base catalyst for next use. Product detection shows that the hydroxyl value is 40mgKOH / g, and the theoretical hydroxyl value is 50mgKOH / g. The mass percentage of pentaerythritol phosphite diol in the product is about 80.0%

[0090] The pentaerythritol phosphite diol mixture obtained above was prepared into component S1 according to the following proportions:

[0091]

[0092] The hydroxyl value of the S1 component is 405 mgKOH / g.

[0093] The S2 component is commercially available hexamethylene diisocyanate trimer (HDI trimer, TPA100 brand of Asahi Chemical Co., Ltd., Japan, NCO%=22.5%).

[0094] The weight ratio of component S1 to component S2 is 100:135, calculated based on the molar ratio of hydroxyl to isocyanate being 1.0:1.0.

[0095] The winding process was used to prepare equal-diameter poles with a length of 15m, an outer diameter of 250mm, and an inner diameter of 230mm. After curing, 50mm*100mm samples were cut from them for UV light aging tests.

[0096] Comparative Example

[0097] In Comparative Examples 1-3, pentaerythritol phosphite diol was replaced with dipentaerythritol diphosphite flame retardant, and synthesis and purification were performed according to the method in the literature (Zhou Hao, Wang Dan, Zhang Shilei, et al. Synthesis of dipentaerythritol diphosphite flame retardant [J]. Journal of Nanjing Normal University <Engineering Technology Edition>. 2010 (10) 48-52), so as to compare the mechanical properties and flame retardant properties with those of Examples 1-3. The remaining formula ratios, sample preparation and test conditions were consistent with those of the corresponding Examples 1-3.

[0098] In Comparative Examples 4-6, all pentaerythritol phosphite diols were replaced with phosphate polyol reactive flame retardants without a ring structure, and the structures are shown below:

[0099]

[0100] The flame retardant manufacturer is: Changhe Chemical New Materials (Jiangsu) Co., Ltd., brand name 430, in order to compare the hydrolysis resistance and UV aging resistance with Examples 4-6. The remaining formula proportions, sample preparation and test conditions are consistent with the corresponding Examples 4-6.

[0101] Performance comparison:

[0102]

[0103] Oxygen index test standard: GB / T 8924-2005; flexural performance test standard: GB / T 1449-2005; tensile performance test standard: GB / T 1447-2005.

[0104] It can be seen that the performance of Comparative Examples 1-3 is basically consistent with that of the corresponding embodiments, and the phosphite pentaerythritol diol ester mixture prepared by the low-cost manufacturing process of the present invention can basically achieve the application effect of adding dipentaerythritol diphosphite flame retardant. However, the flame retardant of Comparative Examples 1-3 is an additive type, and there is still a problem of flame retardant migration during the use of the product, which leads to a decrease in the mechanical properties and flame retardant properties of the product after long-term migration.

[0105]

[0106]

[0107] The damp heat aging conditions are 85°C, 85% RH for 1000h. The retention rate of mechanical properties before and after aging is tested. The reference standard is IEC 61215, 10.13.

[0108] Mechanical properties retention rate test standard: GB / T 1447-2005.

[0109] UV aging conditions: wavelength: 280 ~ 320nm, intensity: 1500kW·h / m 2 , duration: 2000h, test the retention rate of mechanical properties before and after aging, reference standard: IEC 61215-2:2016.

[0110] It can be seen that the mechanical property retention rate of the embodiment and the corresponding comparative examples 4-6 is significantly improved, which fully demonstrates that the cyclic polyol structure provided by the present invention provides excellent hydrolysis resistance and light aging resistance for the cured product and the composite material.

Claims

1. A pentaerythritol phosphite diol, characterized in that: The pentaerythritol phosphite diol has a structure as shown in formula (I): In formula (I), R1 is C2-C 18 The straight-chain alkyl, branched-chain alkyl, cyclic alkyl or aryl group is selected from the group consisting of: HO-R1-OH and HO-R2-OH; or HO-R1-OH is a polyether diol or polyester diol having a molecular weight of 200-1000 g / mol.

2. The pentaerythritol phosphite diol according to claim 1, characterized in that The polyether diol is polypropylene oxide ether diol; the polyester diol is one of polyethylene adipate diol, polybutylene adipate diol, polyneopentyl adipate diol and polyhexane adipate diol.

3. A method for preparing the pentaerythritol phosphite diol according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: Adding triester phosphite, transesterification catalyst and pentaerythritol into a three-necked flask connected to a condenser to receive the fraction, sealing, heating to 120-160° C., reacting for 6 hours, and continuing to add diol at the same temperature, and continuing to react for 6 hours. After almost no fraction is evaporated, filtering out the transesterification catalyst to obtain pentaerythritol phosphite diol or a mixture A thereof; wherein the mixture A contains ≥78wt% of pentaerythritol phosphite diol; The phosphite triester structure is as follows: R is a C1-C4 aliphatic chain.

4. A two-component aliphatic polyurethane resin, the polyurethane resin is prepared by mixing component S1 and component S2, characterized in that: The S1 component contains the pentaerythritol phosphite diol according to claim 1, and the S2 component is isocyanate or a prepolymer of isocyanate.

5. The polyurethane resin according to claim 3 is characterized in that The ratio of the molar number of the reactive hydroxyl group in the S1 component to the molar number of the reactive isocyanate in the S2 component is (1.0-1.1):1.0; the S1 component comprises the following raw materials in parts by weight: The mixture A contains ≥78 wt % of pentaerythritol phosphite diol.

6. The polyurethane resin according to claim 5, characterized in that The hydroxyl value of the pentaerythritol phosphite diol or its mixture A is 40-300 mgKOH / g; the hydroxyl value of the S1 component is 276-411 mgKOH / g; the polyether polyol is one or more polypropylene oxide ether polyols with a functionality f=3-6 and a hydroxyl value of 280-650 mgKOH / g.

7. The polyurethane resin according to claim 5, characterized in that The release agent is selected from one of 1948MCH, 1968MCH of AXEL Company of the United States, HB-550, and HB-550D of Ken-Trend Company of the United States; the catalyst A is an organic tin compound with low catalytic activity; the flame retardant is selected from one of triethyl phosphate, tris-(1,3-dichloroisopropyl) phosphate, tris-(chloroisopropyl) phosphate, and tris(butoxyethyl) phosphate.

8. The method for preparing an aliphatic polyurethane resin according to any one of claims 5 to 7, characterized in that: The method comprises the following steps: mixing component S1 and component S2, and obtaining the polyurethane resin after curing; The preparation of component S1 comprises the following steps: (1) adding triester phosphite, ester exchange catalyst and pentaerythritol into a three-necked flask connected to a condenser to receive distillate, sealing, heating to 120-160° C., reacting for 6 hours, adding diol at the same temperature, and continuing to react for 6 hours, filtering out the ester exchange catalyst after almost no distillate is evaporated, and obtaining pentaerythritol phosphite diol or a mixture A thereof, and testing its hydroxyl value; (2) according to the hydroxyl value data in step (1), adding other different types of polyether polyols, and adjusting the hydroxyl value to 400-450 mgKOH / g; (3) continuing to add auxiliary agents and stirring evenly, the auxiliary agents include a release agent, a catalyst A and a flame retardant; the molar ratio of the added amount of the triester phosphite, pentaerythritol and diol in step (1) is 1:0.5:1, and the amount of the transesterification catalyst added is 5wt% of the amount of the triester phosphite added; The phosphite triester structure is as follows: R is a C1-C4 fatty chain; The transesterification catalyst is a solid alkaline catalyst; The diol is C2-C 18 aliphatic diols or polyether diols or polyester diols having a molecular weight of 200-1000 g / mol.

9. The preparation method according to claim 8, characterized in that: The transesterification catalyst is selected from the 8XMP model of Tulsimer Company of the United States or the A-21 model product of Jiangyin Nanda Synthetic Company.

10. A fiber-reinforced material, prepared by combining the aliphatic polyurethane resin according to any one of claims 1 to 7 with fibers.